2016
DOI: 10.1016/j.ultsonch.2015.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanism of dual-frequency power ultrasound on the molecular weight distribution of corn gluten meal hydrolysates

Abstract: The impact of dual-frequency power ultrasound (DPU) on the molecular weight distribution (MWD) of corn gluten meal (CGM) hydrolysates and its mechanism were investigated in the present study. The mechanism was studied from aspects of structural and nano-mechanical characteristics of the major protein fractions of CGM, viz. zein and glutelin. The results of molecular weight distribution indicated that DPU pretreatment of CGM was beneficial to the preparation of peptides with molecular weights of 200-1000Da. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 35 publications
0
55
0
Order By: Relevance
“…Thirty‐nine oligopeptides were identified in PPF treated by HPM of 120 MPa, while control and 210 MPa had the less oligopeptide composition of 29 and 35, respectively. The results were in accordance with MWD, TCA‐NSI and DH, which suggested that disaggregation possibly promoted exposure of normally hindered cleavage sites in native protein (Zhong et al ., ; Jin et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty‐nine oligopeptides were identified in PPF treated by HPM of 120 MPa, while control and 210 MPa had the less oligopeptide composition of 29 and 35, respectively. The results were in accordance with MWD, TCA‐NSI and DH, which suggested that disaggregation possibly promoted exposure of normally hindered cleavage sites in native protein (Zhong et al ., ; Jin et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of plant protein isolates contain denatured proteins, due to the commonly applied industrial processes (Joshi et al ., ; Liu et al ., ,b), which lead to the traditional enzymolysis has many drawbacks such as low conversion rate of the substrate, longer reaction time and high energy consumption (Qu et al ., ). Thus, some pretreatment technologies as ultrasound (Jia et al ., ; Qu et al ., ; Uluko et al ., ; Jin et al ., ,b), high hydrostatic pressure (Quirós et al ., ; Zhang et al ., ), heat treatment (Zhang et al ., ), microwave (Izquierdo et al ., ), extrusion (Wang et al ., ) and pulsed electric field (Toepfl et al ., ) have been used to enhance the hydrolysis of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…3.5. Effect of ultrasound-assisted acid on the surface morphology of SPI Atomic force microscope (AFM) is a powerful tool to measure the surface morphology, particle size and distribution, which are always related to functional properties of protein (Jin et al, 2016;Lin et al, 2014;Zhang et al, 2016). The AFM images of SPI treated by ultrasound and acid are shown in Fig.…”
Section: Sds-page Analysismentioning
confidence: 99%
“…This increase in the amounts of small peptides fraction (200-3000 Da) after ultrasound pretreatment might be due to exposure of more hydrophobic cores buried inside the protein. Moreover, Alcalase is a typical endoprotease with a preference for sites containing hydrophobic residues [31]. You et al [32] also reported that the peptides were absorbed by the body mainly in the form of tetrapeptide, tripeptide, and dipeptide, rather than mainly 4 Journal of Food Quality Note.…”
Section: Molecular Weight Distribution and Amino Acids Profile After mentioning
confidence: 99%